Building Real-Time Collaborative Applications with a Federated Architecture - Ojanguren-Menendez, Pablo; Tenorio-Fornés, Antonio; Hassan, Samer (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
Real-time collaboration is being offered by multiple libraries and APIs (Google Drive Real-time API, Microsoft Real-Time Communications API, TogetherJS, ShareJS), rapidly becoming a mainstream option for webservices developers. However, they are offered as centralised services running in a single server, regardless if they are free/open source or proprietary software. After re-engineering Apache Wave (former Google Wave), we can now provide the first decentralised and federated free/open source alternative. The new API allows to develop new real-time collaborative web applications in both JavaScript and Java environments.
Keywords: collaboration; real-time locating systems; API; federation; apache; IJIMAI